Penerapan Metode Praktikum dan Simulasi pada Materi Ekosistem di SMA Negeri 2 Bae Kudus - Saida, Nadhifatu Umaru; Iswari, Retno Sri; Pukan, Krispinus Kedati (Journal of Biology Education, 2018)
Teaching and Learning process through practice and simulation method direct the students to understand the concept better. This research aimed to find out the studentsâ achievement in the implementation of practice and simulation method on the ecosystem material as well as the studentsâ attitude toward the method given. The design of this research was quasi-experimental research. The population of this research was tenth-grade students of senior high school 2 Bae Kudus.The purposive sampling technique was used to choose the sample. The sample that is chosen was X MIPA 3 class (experimental class) and X MIPA 4 (Control class). Based on t-test result, the value of significance (2-tailed) amount 0,00 was obtained. Thedataof this research showed the value of significance < 0,05. It was proved that there is a significant difference on the studentsâ achievement between the experimental class and the control class.The studentsâ achievement average of the experimental class was 77,78 and the average in the control class was 57,02.Total of the students who gave the positive response toward practice and simulation method was 77,78%. The implementation of the practice and simulation method directed the students to understand the material being studied better so the studentsâ achievement becomes optimum.